The formula of g(x) is g(x) = -0.8x - 1.6
<h3>How to determine the
formula of g(x)?</h3>
The equation is given as:
-4x - 6 = 5y + 2
Subtract 2 from both sides
5y = -4x - 8
Divide through by 5
y = -0.8x - 1.6
Express as a function
g(x) = -0.8x - 1.6
Hence, the formula of g(x) is g(x) = -0.8x - 1.6
Read more about linear functions at:
brainly.com/question/4025726
#SPJ1
Answer:
5
Step-by-step explanation:
We know that a^2+b^2=c^2 from the Pythagorean theorem where a and b are the legs and c is the hypotenuse
4^2+3^2 = c^2
16+9 = c^2
25 = c^2
Taking the square root of each side
sqrt(25) = sqrt(c^2)
5 =c
Answer:
honestly math is my worst subject but i think its 2 im really srry i think thats wrong tho
Step-by-step explanation:
Answer:
Directrix equation: y = 11/2
y = k - c = 6 - 1/2 = 11/2
Step-by-step explanation:
y=(1/2) x^2+6x+24
factor this
y = (1/2)* [ x^2 + 12x ] + 24
y = (1/2)* [ x^2 + 12x + 36 - 36] + 24
y = (1/2)* [ (x + 6)^2 - 36] + 24
y = (1/2)* (x + 6)^2 - 18 + 24
y = (1/2)* (x + 6)^2 + 6
y - 6 = (1/2)* (x + 6)^2
2*(y - 6) = (x + 6)^2
4c = 2, (h, k) = (-6, 6)
c = 1/2
Directrix equation: y = k - c = 6 - 1/2 = 11/2